Hubungan Status Perokok dengan Nilai Saturasi Oksigen (SpO2) Pasca Anestesi Umum di Rumah Sakit Khusus Bedah Jatiwinangun - Menik Intan Safitri; Danang Tri Yudono; Linda Yanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Smoking is a risk factor that can impact blood oxygen saturation levels and respiratory system performance. Smoking raises the risk of reduced postoperative oxygen saturation in individuals receiving general anaesthesia. The purpose of this study is to ascertain the relationship between smoking status and oxygen saturation (SpO2) levels at the Jatiwinangun Special Surgery Hospital during general anaesthesia. This study employed a cross-sectional methodology and a quantitative design. There were 49 responders in the sample. The Chi-Square test was used to analyse the data that had been gathered through observation and medical record documentation. According to the findings, up to 24 respondents (49.0%) were young adults (20–39 years old). In terms of gender, 30 respondents (61.2%) were female, whereas just 19 respondents (38.8%) were male. Up to 25 respondents (51.0%) were active smokers. Oxygen saturation was abnormal in 26 respondents (53.1%) (<95%). The results of the chi-square test revealed a significant correlation between smoking status and oxygen saturation levels during general anaesthesia, with a p-value of 0.004 (p < 0.05). In comparison to non-smokers, patients with a history of smoking are more likely to experience decreased oxygen saturation.